Role of Different Cytokinins and Auxins for Micropropagation, Callogenesis and Plant Regeneration in Lilium (Lilium longiflorum) - Ali, Aamir; Yasmin, Saira; Shaheen Niazi, Rabia; Majid, Abdul; Huma Naveed, Naima (Asian Journal of Chemistry, 2012)
In vitro propagation of Lilium longiflorum was carried out to explore its potential for micropropagation and callogenesis using meristem and twin scales explants and to study the influence of different concentrations and combinations of various phytoharmones along with varying physical factors like temperature and light. MS medium supplemented with 2 mg/L of BAP was found to be best for shoot formation from meristem, with 84 % shoot formation within 12 days of meristem inoculation while in case of twin scales, 88 % shoot initiation response was obtained on MS medium containing 1.5 mg/L of BAP with 0.5 mg/L of NAA after 12 days of inoculation. Maximum shoot multiplication response was obtained at 3 mg/L of Kinetin with an average of 4.8 shoots per culture vial after 8.2 days of inoculation. The best in vitro rooting response was obtained on MS medium supplemented with 1.5 mg/L of NAA i.e. an average of 5.2 roots were formed after 12 days of inoculation with an average root length of 1.76 cm. When well developed in vitro plants were shifted for hardening on different media (sand, silt, peat, sand+ peat and sand+ silt+ peat in the ratio of 1:1, 1:1:1 respectively). 100 % Hardening response was recorded on Peat. Maximum callus induction response (88 %) was obtained from twin scale explant after 9.8 days of inoculation on MS supplemented with 2.0 mg/L of NAA + 0.25 mg/L of BAP. A temperature of 26 ºC and photoperiod of 16 h/8 h light/dark in every 24 h cycle showed best response for in vitro culturing of Lilium.